HENRIK HAJDUS (1890–1969) ROLLE I UDBREDELSEN AF DET 19. OG 20. ÅRHUNDREDES DANSKE LITTERATUR I UNGARN - Csúr, Gábor Attila (Folia Scandinavica Posnaniensia, 2017)
The Hungarian literary translator Henrik Hajdu (1890–1969) was one of the most extraordinary persons in the history of translating Scandinavian literature into Hungarian. Aside his activity as a translator from Norwegian and Swedish, Hajdu was also an important promoter of Danish authors of the 19th and 20th century. He held lectures on Nordic culture and literature, wrote reviews in prominent Hungarian journals and maintained regular contact to many of the Scandinavian publishers, writers, dramatists and poets. He translated novels by Henrik Pontoppidan, Martin Andersen Nexø and Sigrid Undset, made an edition of Ibsen's complete works and a great amount of short stories and poems. His oeuvre numbers about a hundred separate publications. This paper focuses on how he contributed to the general acceptance and reception of Danish literary works written between 1850 and 1930 among the Hungarian readers.